2018
DOI: 10.3389/fgene.2018.00391
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Selection for Growth Traits in Pacific Oyster (Crassostrea gigas): Potential of Low-Density Marker Panels for Breeding Value Prediction

Abstract: Pacific oysters are a key aquaculture species globally, and genetic improvement via selective breeding is a major target. Genomic selection has the potential to expedite genetic gain for key target traits of a breeding program, but has not yet been evaluated in oyster. The recent development of SNP arrays for Pacific oyster (Crassostrea gigas) raises the opportunity to test genomic selection strategies for polygenic traits. In this study, a population of 820 oysters (comprising 23 full-sibling families) were g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
71
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(81 citation statements)
references
References 54 publications
7
71
3
Order By: Relevance
“…Atlantic salmon (Ødegård et al ; Tsai et al ; Yoshida et al ; Robledo et al ), rainbow trout (Vallejo et al ; Yoshida et al ), sea bream (Palaiokostas et al ) and sea bass (Palaiokostas et al ). Further, in shellfish similar findings have been observed for prediction of breeding values for growth traits in scallop (Dou et al ) and Pacific oyster (Gutierrez et al ). Therefore, the technical potential of genomic selection for expedited genetic improvement in shellfish has been shown.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Atlantic salmon (Ødegård et al ; Tsai et al ; Yoshida et al ; Robledo et al ), rainbow trout (Vallejo et al ; Yoshida et al ), sea bream (Palaiokostas et al ) and sea bass (Palaiokostas et al ). Further, in shellfish similar findings have been observed for prediction of breeding values for growth traits in scallop (Dou et al ) and Pacific oyster (Gutierrez et al ). Therefore, the technical potential of genomic selection for expedited genetic improvement in shellfish has been shown.…”
Section: Discussionsupporting
confidence: 80%
“…Moreover, a high-density linkage map containing 20 000 SNPs has recently been created and aligned with the physical reference genome assembly (Zhang et al 2012;Gutierrez et al 2018a). Using such arrays, several studies have demonstrated that genomic selection for aquaculture species results in improved accuracy compared with traditional pedigree-based approaches; for example in Atlantic salmon (Robledo et al 2018), coho salmon (Barr ıa et al 2018), rainbow trout (Vallejo et al 2018), common carp (Palaiokostas et al 2018b) and Pacific oyster (Gutierrez et al 2018b).…”
Section: Introductionmentioning
confidence: 99%
“…This result has been mirrored in other studies of genomic versus pedigree-based prediction of disease resistance breeding values for other important farmed fish species, e.g Atlantic salmon (Tsai et al 2015; Yoshida et al 2017; Ødegård et al 2014; Robledo et al 2018), rainbow trout (Vallejo et al 2017; Yoshida et al 2018), sea bream (Palaiokostas et al 2016) and sea bass (Palaiokostas et al 2018a). Further, in shellfish similar findings have been observed for prediction of breeding values for growth traits in scallop (Dou et al 2016) and Pacific oyster (Gutierrez et al 2018b). Therefore, the technical potential of genomic selection for expedited genetic improvement in shellfish has been shown.…”
Section: Discussionsupporting
confidence: 80%
“…Moreover, a high density linkage map containing ∼20K SNPs has recently been created and aligned with the physical reference genome assembly (Gutierrez et al 2018a; Zhang et al 2012). Using such arrays, several studies have demonstrated that genomic selection for aquaculture species results in improved accuracy compared to traditional pedigree-based approaches; for example in Atlantic salmon (Robledo et al 2018), coho salmon (Barría et al 2018), rainbow trout (Vallejo et al 2018), common carp (Palaiokostas et al 2018b), and Pacific oyster (Gutierrez et al 2018b).…”
Section: Introductionmentioning
confidence: 99%
“…Signatures of selection that are different between natural and farmed populations, including markers under domestication selection, can indicate specific genomic regions or markers that have been selected for during the domestication or selective breeding process (Gutierrez et al, 2016; Gutierrez et al, 2018). Here it is not possible to determine whether the outliers identified were under selection on the farms or hatchery, or whether they have relaxed selection from what they would be exposed to in nature.…”
Section: Discussionmentioning
confidence: 99%